PENGEMBANGAN MEDIA PEMBELAJARAN SCRAMBLE POP UP UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PADA SISWA KELAS 1 SEKOLAH DASAR NEGERI KAPI 2 - Shintya Ika Rahma; Sutrisno Sahari; Nursalim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop a Scramble Pop-Up learning media to improve the early reading skills of first-grade students at SDN Kapi 2. The main problem addressed is the low student motivation and the lack of engaging learning activities. The development aims to assess the validity, practicality, and effectiveness of the media. The method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Limited trials were conducted with 8 students, while wider trials involved 18 students. Data were collected through observation, interviews, documentation, expert questionnaires, pre-tests, and post-tests. The validation results indicated that the media was highly valid (92% from content experts, 95% from media experts), with an average score of 94%. Practicality was demonstrated by 100% positive student responses, stating that the media was engaging and easy to use. The N-Gain score for effectiveness was 0.80 (limited trial) and 0.88 (wider trial), which falls into the high category. Therefore, the Scramble Pop-Up media is considered valid, practical, and effective in enhancing the early reading skills of first-grade students.